CoVID‐19: Parent and caregiver concerns about reopening New Zealand schools. (28th October 2020) - Jeffs, Emma; Lucas, Nathanael; Walls, Tony
Abstract : Aim: Children generally have a milder CoVID‐19 disease course and better prognosis than adults. Many countries have closed schools as part of measures to limit transmission and this has had a considerable impact on children world‐wide. This includes New Zealand (NZ), where rates of CoVID‐19 have been very low. The aims of this study were to investigate parents' and caregivers' knowledge of CoVID‐19 in children, to understand their levels of concern and to identify their most trusted sources of information. Methods: Participants were recruited via NZ parenting support and interest groups on Facebook.com . Knowledge was assessed by way of a self‐administered questionnaire during the 10 days prior to NZ schools reopening on 18 May 2020. Results: Of the 1191 study participants, 721 (60%) expressed some level of worry (14.5% very or extremely worried) that their child would catch CoVID‐19 at school. A high proportion (79%, 941) thought it likely or very likely that their child would catch CoVID‐19 at school if there were to be widespread community transmission. Fear scores for CoVID‐19 were generally high, and 828 (80%) of participants said they would vaccinate their child if a newly developed vaccine were available. Conclusions: Parents and caregivers were generally fearful of their children acquiring CoVID‐19 at school. This was despite messaging from multiple trusted sources that transmission in schools is unlikely, and the number of NZ CoVID‐19 cases being extremely low. These findings have implications for policy development and public health messaging both in NZ and in countries with ongoing community transmission of CoVID‐19.